2015
DOI: 10.1016/j.cell.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine Modulates Messenger RNA Translation Efficiency

Abstract: SUMMARY N6-methyladenosine (m6A) is the most abundant internal modification in mammalian mRNA. This modification is reversible and non-stoichiometric and adds another layer to the dynamic control of mRNA metabolism. The stability of m6A-modified mRNA is regulated by an m6A reader protein, human YTHDF2, which recognizes m6A and reduces the stability of target transcripts. Looking at additional functional roles for the modification, we find that anotherm6A reader protein, human YTHDF1, actively promotes protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
3,270
7
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 2,770 publications
(3,352 citation statements)
references
References 61 publications
69
3,270
7
6
Order By: Relevance
“…The change in the level of m6A modifiers in old PBMCs and senescent HDFs implies their involvement in mammalian aging and cellular senescence (Figures 4d and 5h). Dynamic regulation of m6A modification and mRNA decay is also dictated by position‐specific m6A methylation within the mRNA, and presence/activity of m6A‐binding proteins within a given context (Alarcón et al., 2015; Wang & He, 2014; Wang et al., 2014, 2015). A possibility is that DROSHA mRNA methylation is maintained by the presence of m6A readers or m6A‐regulated factors such as HuR, FMR1, and G3BP, resulting in preservation of DROSHA mRNA levels during the aging process (Edupuganti et al., 2017; Visvanathan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The change in the level of m6A modifiers in old PBMCs and senescent HDFs implies their involvement in mammalian aging and cellular senescence (Figures 4d and 5h). Dynamic regulation of m6A modification and mRNA decay is also dictated by position‐specific m6A methylation within the mRNA, and presence/activity of m6A‐binding proteins within a given context (Alarcón et al., 2015; Wang & He, 2014; Wang et al., 2014, 2015). A possibility is that DROSHA mRNA methylation is maintained by the presence of m6A readers or m6A‐regulated factors such as HuR, FMR1, and G3BP, resulting in preservation of DROSHA mRNA levels during the aging process (Edupuganti et al., 2017; Visvanathan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…indicated that YTH domain family protein 2 (YTHDF2) selectively bound to m 6 A‐containing mRNA, subsequently reducing the stability of the target transcripts and affecting the degradation of the mRNA 4. In contrast, YTH domain family protein 1 (YTHDF1) exerts its role in promoting translation efficiency 27. In the meantime, the role of YTH domain‐containing protein 1 (YTHDC1) in regulating mRNA splicing has been revealed 28, 29.…”
Section: The Discovery Of M6a and Its Functionmentioning
confidence: 99%
“…N 6‐methyladenosine (m 6 A) is the most prevalent internal mRNA modification found in eukaryotes, and has received a burst of interest in recent years (Meyer & Jaffrey, 2014; Fray & Simpson, 2015; Yue et al ., 2015). m 6 A appears to be involved in a broad range of biological processes including mRNA export from the nucleus (Fustin et al ., 2013), regulation of splicing (Alarcón et al ., 2015b; Haussmann et al ., 2016; Lence et al ., 2016), mRNA translatability and stability (Wang et al ., 2014a,b, 2015; Bodi et al ., 2015; Zhou et al ., 2015), alternative polyadenylation site choice (Ke et al ., 2015) and other mechanisms accompanying RNA maturation (Meyer & Jaffrey, 2014; Yue et al ., 2015). m 6 A is essential for the earliest stages of pattern formation in plants (Zhong et al ., 2008; Bodi et al ., 2012; Shen et al ., 2016) and metazoans (Meyer & Jaffrey, 2014; Geula et al ., 2015; Yue et al ., 2015; Haussmann et al ., 2016; Lence et al ., 2016), linked with diseases in humans and other mammalian species (Jia et al ., 2011; Zheng et al ., 2013) and is required for meiosis in Saccharomyces cerevisiae (Clancy et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%